2011
DOI: 10.1590/s0103-40142011000100012
|View full text |Cite
|
Sign up to set email alerts
|

Conservação de áreas naturais em São Paulo

Abstract: O argumento central deste texto é a conexão entre as áreas ambientalmente protegidas, sua importância no contexto de uma metrópole mundial e os conflitos decorrentes do crescimento da população metropolitana. Em cidades como São Paulo, a presença de vegetação é um patrimônio, um indicador de qualidade de vida levado em conta pelo mercado imobiliário. Assim, o primeiro objetivo deste texto é analisar a perspectiva territorial da proteção ambiental, referindo-se ao ordenamento interno da grande metrópole e às aç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 2 publications
0
5
0
5
Order By: Relevance
“…The SPMR is Brazil's most important economic and industrial center. It occupies an area of 7946 km 2 , of which one third is urbanized [33][34][35]. Its population rose from 2 million inhabitants in 1940 to 12.6 million in 1980 and to nearly 20 million in 2014, making it the world's fourth most populous metropolis nowadays [9].…”
Section: Study Areamentioning
confidence: 99%
“…The SPMR is Brazil's most important economic and industrial center. It occupies an area of 7946 km 2 , of which one third is urbanized [33][34][35]. Its population rose from 2 million inhabitants in 1940 to 12.6 million in 1980 and to nearly 20 million in 2014, making it the world's fourth most populous metropolis nowadays [9].…”
Section: Study Areamentioning
confidence: 99%
“…There are many studies regarding the management of green urban areas in the Municipality of São Paulo (PHILIPPI JR. and BRUNA, 1998;SILVA FILHO, 2005, COELHO, 2008MELLO-THÉRY, 2011;SEPE and PEREIRA, 2012;LIMNIOS and FURLAN, 2013). However, no studies were found that focus on the management of green areas as a whole, encompassing legal, economic, administrative and institutional instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Dessa forma, caso as políticas de gestão e planejamento, voltadas para a manutenção dos fragmentos florestais, unidades de conservação e áreas de preservação permanente não forem providenciadas, o futuro projeta condições pouco promissoras do ponto de vista ambiental, para as cidades em desenvolvimento (MELLO-THÉRY, 2011).…”
Section: Introductionunclassified